The impact of undergraduate degrees on lifetime earnings - Jack Britton; Lorraine Dearden; Laura van der Erve; Ben Waltmann (Institute for Fiscal Studies (IFS), 2020)
Going to university is a very good investment for most students. Over their working lives, men will be 130,000 better off on average by going to university after taxes, student loan repayments and foregone earnings are taken into account. For women, this figure is 100,000. (These and other numbers are in "discounted present value" terms, which means counting earnings later in life less than those earned earlier on. Without discounting, returns look much bigger.) However, these average returns mask large differences across individuals. So while about 80% of students are likely to gain financially from attending university, we estimate that one in five students - or about 70,000 every year - would actually have been better off financially had they not gone to university. At the other end of the spectrum, the 10% of graduates with the highest returns will on average gain around half a million pounds in discounted present value terms. Much of this variation is explained by the subject studied at university: students of medicine and law, for example, achieve very high returns on average, while few of those studying creative arts will gain financially from their degrees at all. These are among the findings of new work at the Institute for Fiscal Studies (IFS) commissioned by the Department for Education that investigates the lifetime returns to undergraduate degrees using the Longitudinal Education Outcomes (LEO) dataset. We control for students' prior attainment and family background to estimate the causal effect of going to university on earnings and employment.
Keywords: 330; Bildungsertrag; Akademiker; Lebenseinkommen; Steuer; Großbritannien